Nicotinamide adenine dinucleotide suppresses epileptogenesis at an early stage - Liu, Juan (Sci Rep, 2017)
The pathophysiologic mechanisms of epileptogenesis are poorly understood, and no effective therapy exists for suppressing epileptogenesis. Numerous reports have shown that nicotinamide adenine dinucleotide (NAD(+)) has neuroprotective effects, suggesting its potential use for treating epileptogenesis. Here we evaluated the effects of NAD(+) on epileptogenesis and the mechanisms underlying these effects. In pilocarpine-induced status epilepticus (SE) model mice, NAD(+) was injected three times within 24.5 h after SE. NAD(+) intervention significantly reduced the incidence of spontaneous recurrent seizure (SRS) and abnormal electroencephalogram (EEG) activity, rescued contextual fear memory formation, reduced neuronal loss in the CA1 region of the hippocampus at SRS stage. Furthermore, exogenous supply of NAD(+) distinctly reversed the seizure-induced depletion of endogenous NAD(+), reduced neuronal apoptosis in the CA1 region of the hippocampus, and reversed the augmented Acp53/p53 ratio at the early stage of epileptogenesis. Our findings demonstrated that early-stage intervention with NAD(+) prevents epileptogenesis in pilocarpine-induced SE mice by suppressing neuronal apoptosis.